Development and Validation of a Tool to Identify Patients With Type 2 Diabetes at High Risk of Hypoglycemia-Related Emergency Department or Hospital Use - Karter, Andrew J. (JAMA Intern Med, 2017)
IMPORTANCE: Hypoglycemia-related emergency department (ED) or hospital use among patients with type 2 diabetes (T2D) is clinically significant and possibly preventable. OBJECTIVE: To develop and validate a tool to categorize risk of hypoglycemic-related utilization in patients with T2D. DESIGN, SETTING, AND PARTICIPANTS: Using recursive partitioning with a split-sample design, we created a classification tree based on potential predictors of hypoglycemia-related ED or hospital use. The resulting model was transcribed into a tool for practical application and tested in 1 internal and 2 fully independent, external samples. Development and internal testing was conducted in a split sample of 206 435 patients with T2D from Kaiser Permanente Northern California (KPNC), an integrated health care system. The tool was externally tested in 1 335 966 Veterans Health Administration and 14 972 Group Health Cooperative patients with T2D. EXPOSURES: Based on a literature review, we identified 156 candidate predictor variables (prebaseline exposures) using data collected from electronic medical records. MAIN OUTCOMES AND MEASURES: Hypoglycemia-related ED or hospital use during 12 months of follow-up. RESULTS: The derivation sample (n = 165 148) had a mean (SD) age of 63.9 (13.0) years and included 78 576 (47.6%) women. The crude annual rate of at least 1 hypoglycemia-related ED or hospital encounter in the KPNC derivation sample was 0.49%. The resulting hypoglycemia risk stratification tool required 6 patient-specific inputs: number of prior episodes of hypoglycemia-related utilization, insulin use, sulfonylurea use, prior year ED use, chronic kidney disease stage, and age. We categorized the predicted 12-month risk of any hypoglycemia-related utilization as high (>5%), intermediate (1%-5%), or low (<1%). In the internal validation sample, 2.0%, 10.7%, and 87.3% were categorized as high, intermediate, and low risk, respectively, with observed 12-month hypoglycemia-related utilization rates of 6.7%, 1.4%, and 0.2%, respectively. There was good discrimination in the internal validation KPNC sample (C statistic = 0.83) and both external validation samples (Veterans Health Administration: C statistic = 0.81; Group Health Cooperative: C statistic = 0.79). CONCLUSIONS AND RELEVANCE: This hypoglycemia risk stratification tool categorizes the 12-month risk of hypoglycemia-related utilization in patients with T2D using only 6 inputs. This tool could facilitate targeted population management interventions, potentially reducing hypoglycemia risk and improving patient safety and quality of life.